PENGARUH ANGGARAN BERBASIS KINERJA TERHADAP PENINGKATAN KINERJA APARATUR PEMERINTAH DAERAH - RAMAYANI LANDE; CORNELIUS RANTELANGI; FERRY DIYANTI (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2016)
Performance-based budgeting to achieve governance in Indonesia, the principles of Performance-based budgeting should be enforced in a variety of important institutions of governance, both central and local government. The problems of this research: What effect on the performance-based budget performance improvement local government apparatus. This study aims to determine the effect of performance-based budgeting to the improved performance of local government officials empirical study on Department of Hygiene and Samarinda. The method used in this research is quantitative method. The sample in this research that the Department of Hygiene and Samarinda, head of department, secretaris, head of the finance department and its sub-staff financial officer, the head of the field, and the section head directly involved in the budget process as a respondent. Sampling technique used is purposive samling and techniques of collecting data obtained through questionnaires or questionnaires and analysis techniques using Partial Least Square (PLS) with the help of software SmartPLS. The results of this study prove that the Performance-based budgeting with indicators that are sorted from the most influence is that the indicators are sorted from the most influence, namely: transparency and accountability on the budget, Discipline Budget, Justice budget, participatory, had a positive influence on the realization of the increase in the performance of government officials area on the Department of Hygiene and Samarinda.Keywords: Performance-Based Budgeting, Performance Enhancement      Apparatus  Local government